Visible light induced reversible extrusion of nitric oxide from a ruthenium(II) nitrosyl complex: a facile delivery of nitric oxide. - Heinemann, Frank Wilhelm; et al. (Journal of the American Chemical Society, 2005)
The new ruthenium compound [Ru(NO)(pysiS4)]Br (3) (pysiS4 = 2,6-bis(3-triphenylsilyl-2-sulfanylphenylthiomethyl)pyridine), containing sterically bulky SiPh3 groups ortho to the thiolate donors, has been synthesized. In solution, 3 releases NO efficiently on exposure to visible light (lambda >/= 455 nm) at room temperature to afford [Ru(Br)(pysiS4)] (4). Treatment of 4 with NO yielded exclusively 3 without any metal-bound side reaction.